Bye Bye Lisbon: Tourism Gentrification Impacts on Lisbon´s Inner-City Housing Market - Mendes, Luís (2020)
Urban tourism in its various forms has seen a great expansion at the beginning of the 21st century, but the overtourism as a mass phenomenon, hegemonic and dominant in the large Portuguese cities of Lisbon and Porto, is a recent phenomenon. Lisbon is experiencing a peak of international projection as a tourist destination, registering considerable uninterrupted increases in tourist arrivals, overnight stays, and daily revenues, as well as number of hotels, hostels, and short-rental tourist accommodation, with drastic impacts on the social and economic fabric in the historical districts of central Lisbon is recent. This chapter focuses on the driving forces of austerity urbanism and the neoliberal turn in urban politics that fuels the process of tourism gentrification, in the last decade, in Lisbon's historic neighborhoods.